Quality of end‐of‐life care in patients with hematologic malignancies: A retrospective cohort study. Issue 10 (18th February 2014) - Hui, David; Didwaniya, Neha; Vidal, Marieberta; Shin, Seong Hoon; Chisholm, Gary; Roquemore, Joyce; Bruera, Eduardo
<x xml:space="preserve">Abstract</x> BACKGROUND To the authors' knowledge, only limited data are available regarding the quality of end‐of‐life care for patients with hematologic malignancies. In this retrospective cohort study, the quality of end‐of‐life care was compared between patients with hematologic malignancies and those with solid tumors. METHODS All adult patients who died of advanced cancer between September 1, 2009 and February 28, 2010 while under the care of the study institution were included. The authors collected baseline demographics and end‐of‐life care indicators, including emergency room visits, hospitalization, intensive care unit admissions, and systemic cancer therapy use within the last 30 days of life. RESULTS Of a total of 816 decedents, 113 (14%) had hematologic malignancies. In the last 30 days of life, patients with hematologic malignancies were more likely to have emergency room visits (54% vs 43%; P = .03), hospital admissions (81% vs 47%; P < .001), ≥ 2 hospital admissions (23% vs 10%; P < .001), > 14 days of hospitalization (38% vs 8%; P < .001), intensive care unit admissions (39% vs 8%; P < .001) and death (33% vs 4%; P < .001), chemotherapy use (43% vs 14%; P < .001), and targeted therapy use (34% vs 11%; P < .001) compared with patients with solid tumors. Patients with hematologic malignancies were also less likely to have palliative care unit admissions (8% vs 17%; P = .02). The composite score for aggressiveness of care (with 0 indicating the best and 6 indicating the worst) was significantly higher among patients with hematologic malignancies compared with those with solid tumors (median, 2 vs 0; P < .001). On multivariate analysis, hematologic malignancy was found to be a significant factor associated with aggressive end‐of‐life care (odds ratio, 6.6; 95% confidence interval, 4.1‐10.7 [P < .001]). CONCLUSIONS The results of the current study indicate that patients with hematologic malignancies received more aggressive care at the end of life. Cancer 2014;120:1572–1578. © 2014 American Cancer Society.